Influence of Products, Promotion and Distribution of Purchasing Decisions on Fighting Brand Products (S-Tee) PT. Sinar Sosro - Yuli Purwati; Hosni Suradji (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
Abstract— The purpose of this research is to find out the significant influence of marketing factors which consists of product, promotion, and good distribution simultaneously or partially toward fighting brand product (S-tee) for buying decision at PT. Sinar Sosro. The description of the population which is management students in Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) examined the entire customers who buy Fighting brand product (S-tee) at PT. Sinar Sosro with as much as 320 samples of people are taken as respondent. The multiple regression analysis is used as analysis technique in this research in addition to find out the amount of regression coefficient as well as to show the strength influence of a product, promotion, and good distribution simultaneously or partially toward fighting brand product (S-tee) buying decision at PT. Sinar Sosro. The statistic test which is conducted can also be concluded that variable which has dominant influence toward customers’ decision in buying fighting brand product (S-tee) at PT. Sinar Sosro is a good distribution variable since its partial determination coefficient is the highest that is 33.1% compare to other variables.